2016
DOI: 10.1093/hmg/ddw311
|View full text |Cite
|
Sign up to set email alerts
|

The FMR1 promoter is selectively hydroxymethylated in primary neurons of fragile X syndrome patients

Abstract: Fragile X syndrome (FXS) results from a repeat expansion mutation near the FMR1 gene promoter and is the most common form of heritable intellectual disability and autism. Full mutations larger than 200 CGG repeats trigger FMR1 heterochromatinization and loss of gene expression, which is primarily responsible for the pathological features of FXS . In contrast, smaller pre-mutations of 55–200 CGG are associated with FMR1 overexpression and Fragile X-associated tremor/ataxia syndrome (FXTAS), a late-onset neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 75 publications
2
19
0
1
Order By: Relevance
“…The observed increase in BEC FREE2 DNA methylation extends previous studies where FREE2 methylation levels, associated with FM, were elevated in different tissue types, including adult and newborn blood, lymphoblasts, chorionic villi, and primary neurons from post mortem brains 4 , 5 , 7 , 27 30 . Notably, the FREE2 region has also been referred to via a different name – for example FMR1 “down-stream region” as in Esanov et al .…”
Section: Discussionsupporting
confidence: 86%
“…The observed increase in BEC FREE2 DNA methylation extends previous studies where FREE2 methylation levels, associated with FM, were elevated in different tissue types, including adult and newborn blood, lymphoblasts, chorionic villi, and primary neurons from post mortem brains 4 , 5 , 7 , 27 30 . Notably, the FREE2 region has also been referred to via a different name – for example FMR1 “down-stream region” as in Esanov et al .…”
Section: Discussionsupporting
confidence: 86%
“…A long-term question concerns roles in neurons versus glia. A recent study of human patients shows FMR1 epigenetic alterations silence FMRP specifically in neurons, but not glia or neurons obtained from reprogrammed pluripotent stem cells [13]. In the mouse FXS model, recent work shows FMRP loss changes cell differentiation kinetics for both neurons and glia (Table 1) [14], and astrocyte-specific FMRP knockout in mice increases neuronal dendritic spine density similar to the global FXS condition [15].…”
Section: Overview Of Expanding Fmrp Functionsmentioning
confidence: 99%
“…Partnerships with other mRNA-binding proteins could provide the long-sought specificity for coupled control of transcript targets in neuron class-specific mechanisms [4043]. FMRP roles in glia may also contribute to FXS [1315], and this remains an important question. Intercellular glial-neuron signaling, as well as trans -synaptic signaling, may have central roles in FXS neuropathology, which are just coming to light [6367].…”
Section: Part V: Future Directionsmentioning
confidence: 99%
“…This finding is surprising, as previous work suggested that this methylation typically occurs coincident with or after transcriptional silencing. We explored whether this methylation might instead be by hydroxymethylation, which is not transcriptionally silencing (Brasa, Mueller et al 2016, Esanov, Andrade et al 2016). However, our preliminary studies demonstrate no evidence of hydroxymethylation in these FXS cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%